Sound speed in water-saturated glass beads as a function of frequency and porosity - Schröter, Matthias; Argo IV, Theodore F.; Guild, Matthew D.; Wilson, Preston S.; Radin, Charles; Swinney, Harry L. (Journal of the Acoustical Society of America, 2011)
Sound propagation in water-saturated granular sediments is known to depend on the sediment porosity, but few data in the literature address both the frequency and porosity dependency. To begin to address this deficiency, a fluidized bed technique was used to control the porosity of an artificial sediment composed of glass spheres of 265 mu m diameter. Time-of-flight measurements and the Fourier phase technique were utilized to determine the sound speed for frequencies from 300 to 800 kHz and porosities from 0.37 to 0.43. A Biot-based model qualitatively describes the porosity dependence. (C) 2011 Acoustical Society America